Fluorogen-activating proteins: beyond classical fluorescent proteins - Shengnan Xu; Hai-Yu Hu (Elsevier, 2018)
Fluorescence imaging is a powerful technique for the real-time noninvasive monitoring of protein dynamics. Recently, fluorogen activating proteins (FAPs)/fluorogen probes for protein imaging were developed. Unlike the traditional fluorescent proteins (FPs), FAPs do not fluoresce unless bound to their specific small-molecule fluorogens. When using FAPs/fluorogen probes, a washing step is not required for the removal of free probes from the cells, thus allowing rapid and specific detection of proteins in living cells with high signal-to-noise ratio. Furthermore, with different fluorogens, living cell multi-color proteins labeling system was developed. In this review, we describe about the discovery of FAPs, the design strategy of FAP fluorogens, the application of the FAP technology and the advances of FAP technology in protein labeling systems. KEY WORDS: Fluorogen activating proteins, Fluorogens, Genetically encoded sensors, Fluorescence imaging, Molecular imaging